Blockchain Strategy in Improving Transaction Security in The Sharia Capital Market - Ibnu Habib Wahyudi; Imsar; Harahap, Muhammad Ikhsan (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to investigate the strategy of blockchain technology in improving transaction security in the shariah capital market. Using an in-depth interview approach, this research explores the perceptions and understandings of various stakeholders, including industry experts, regulators, and shariah capital market practitioners. Qualitative research methods were used to gain in-depth insights into how blockchain can be applied to strengthen transaction security in the shariah capital market. From the research results, it is concluded that blockchain technology has tremendous potential and relevance in improving transaction security in the Islamic capital market, in this case the use of smart contracts makes a considerable contribution, in its implementation smart contracts can increase security, transparency and efficiency, In the context of the shariah capital market, the principle of